The impact of principals' entrepreneurial leadership behaviour on school organizational innovativeness - Lope Pihie, Zaidatol Akmaliah; Bagheri, Afsaneh (Marsland Press, 2013)
Entrepreneurial leadership has been increasingly applied in various organizations to foster the process of innovation, face the challenges and crises of leadership in the current organization environments and consequently improve the performance of the organizations. However, research on the impact of entrepreneurial leadership on the performance improvement of educational organizations and specifically school organizational innovativeness is scarce. Utilizing a sample of 300 public secondary school teachers in Malaysia, we examined the relationship between principal’s entrepreneurial leadership behaviour and school organizational innovativeness. The data were analysed using Structural Equation Modelling. The results indicated that entrepreneurial leadership behaviour of principals had a significant positive impact on the teachers’ perceived school organizational innovativeness. More specifically, the findings of the study suggest that different aspects of principal’s entrepreneurial leadership behaviour improve the implemented organizational innovations and the changes they created in schools. Implications of the findings for school leadership research and practice are discussed.